Identification of novel therapeutic targets for head and neck squamous cell carcinoma through bioinformatics analysis - Eun-jeong Jeong; Eunjeong Kim; Yeon Soo Kim (Scientific Reports)
Abstract Head and neck squamous cell carcinoma (HNSCC) is a heterogeneous cancer with limited therapeutic options. Using publicly available datasets, we identified the WD repeat domain 54 (WDR54) gene as a potential therapeutic target in HNSCC. Gene expression profiling interactive analysis version 2 (GEPIA2) was used to identify genes differentially overexpressed in HNSCC. Our results showed that WDR54, a member of the WD40 repeat domain family, was overexpressed in HNSCC tumor samples. Analysis of three gene expression omnibus datasets showed that WDR54 was overexpressed in tumor samples. Using the UALCAN database, we showed that WDR54 expression in patients with HNSCC at different tumor stages gradually increased with disease progression. We confirmed the association between WDR54 and metastasis using TNMplot.com. WDR54 was overexpressed in metastatic samples compared to that in normal and tumor samples. Kaplan–Meier analysis showed that patients with high WDR54 levels had a poorer prognosis. Additionally, WDR54 expression was correlated with the epidermal growth factor receptor, which is frequently overexpressed in HNSCC. Our findings suggest that WDR54 is a promising biomarker and therapeutic target in HNSCC.